Is pizza sutable to type 1 diabetes? A real life identification of best compromise between taste and low glycemic index in patients on insulin pump. Issue 3 (May 2020) - Della-Corte, T.; Gentile, S.; Di Blasi, V.; Guarino, G.; Corigliano, M.; Cozzolino, G.; Fasolino, A.; Martino, C.; Improta, M.R.; Oliva, D.; Lamberti, C.; Vecchiato, A.; et al.
Abstract: Opposed to whole wheat (WWP), traditional pizza (TP) is loved by patients with type 1 diabetes mellitus (T1DM) despite causing hyperglycemia. 50 well-trained T1DM patients had higher glucose levels after TP than after WWP or mixed flour pizza, which however was tasty, digestible and metabolically appropriate to break diet monotony. Graphical abstract: Image 1 Highlights: Consumption of traditional pizza causes high post meal glucose levels in patients with diabetes, especially those with type 1 disease. Traditional pizza causes high post meal glucose levels in type 1 diabetes disease. 50 patients with type 1 diabetes, we compared effects of refined (traditional), whole wheat and mixed flour pizzas. The latter two varieties cause lower glucose post meal hyperglycemia, and also have a pleasant taste.